Find the best solutions to your questions at Westonci.ca, the premier Q&A platform with a community of knowledgeable experts. Join our Q&A platform to connect with experts dedicated to providing precise answers to your questions in different areas. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
To find the value of [tex]\( k \)[/tex] in the equation [tex]\( x^2 - 3x + k = 2 \)[/tex], let's follow these steps:
1. Start with the given equation:
[tex]\[ x^2 - 3x + k = 2 \][/tex]
2. Rearrange the equation to isolate [tex]\( k \)[/tex]:
[tex]\[ x^2 - 3x + k - 2 = 0 \][/tex]
This can be rewritten as:
[tex]\[ x^2 - 3x + (k - 2) = 0 \][/tex]
3. Solve for [tex]\( k \)[/tex]:
Now, let's assume a particular value of [tex]\( x \)[/tex] to find [tex]\( k \)[/tex].
Given [tex]\( x = 2 \)[/tex]:
Plug [tex]\( x = 2 \)[/tex] into the equation:
[tex]\[ (2)^2 - 3(2) + (k - 2) = 0 \][/tex]
Simplify this equation step-by-step:
[tex]\[ 4 - 6 + k - 2 = 0 \][/tex]
Combine like terms:
[tex]\[ 4 - 6 - 2 + k = 0 \][/tex]
Simplify further:
[tex]\[ -4 + k = 0 \][/tex]
4. Isolate [tex]\( k \)[/tex]:
Add 4 to both sides of the equation to solve for [tex]\( k \)[/tex]:
[tex]\[ k = 4 \][/tex]
So, the value of [tex]\( k \)[/tex] is:
[tex]\[ k = 4 \][/tex]
1. Start with the given equation:
[tex]\[ x^2 - 3x + k = 2 \][/tex]
2. Rearrange the equation to isolate [tex]\( k \)[/tex]:
[tex]\[ x^2 - 3x + k - 2 = 0 \][/tex]
This can be rewritten as:
[tex]\[ x^2 - 3x + (k - 2) = 0 \][/tex]
3. Solve for [tex]\( k \)[/tex]:
Now, let's assume a particular value of [tex]\( x \)[/tex] to find [tex]\( k \)[/tex].
Given [tex]\( x = 2 \)[/tex]:
Plug [tex]\( x = 2 \)[/tex] into the equation:
[tex]\[ (2)^2 - 3(2) + (k - 2) = 0 \][/tex]
Simplify this equation step-by-step:
[tex]\[ 4 - 6 + k - 2 = 0 \][/tex]
Combine like terms:
[tex]\[ 4 - 6 - 2 + k = 0 \][/tex]
Simplify further:
[tex]\[ -4 + k = 0 \][/tex]
4. Isolate [tex]\( k \)[/tex]:
Add 4 to both sides of the equation to solve for [tex]\( k \)[/tex]:
[tex]\[ k = 4 \][/tex]
So, the value of [tex]\( k \)[/tex] is:
[tex]\[ k = 4 \][/tex]
Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.